2008
DOI: 10.1271/bbb.80154
|View full text |Cite
|
Sign up to set email alerts
|

Mode of Action of the Immunostimulatory Effect of Collagen from Jellyfish

Abstract: We have previously demonstrated that collagen from jellyfish simulated immunoglobulin and cytokine production by human-human hybridoma line HB4C5 cells and by human peripheral blood lymphocytes (hPBL). The mode of action of the collagen as an immunostimulatory factor was investigated. The expression levels of immunoglobulin mRNAs in HB4C5 cells, and those of tumor necrosis factor (TNF)-alpha, interferon (IFN)-gamma, and transforming growth factor (TGF)-beta in hPBL were up-regulated by jellyfish collagen. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 21 publications
2
23
0
1
Order By: Relevance
“…Our previous research showed that collagen from jellyfish N. nomurai enhanced not only the IgM production by the human hybridoma HB4C5 cells, but also the IgM and IgG productions by human peripheral blood lymphocytes by accelerating their gene expression levels. We also confirmed that the IgM production by transcription-suppressed HB4C5 cells was facilitated by jellyfish collagen (Nishimoto et al, 2008). These findings suggest that jellyfish collagen would stimulate not only the transcription but also translational activity.…”
Section: Introductionsupporting
confidence: 79%
“…Our previous research showed that collagen from jellyfish N. nomurai enhanced not only the IgM production by the human hybridoma HB4C5 cells, but also the IgM and IgG productions by human peripheral blood lymphocytes by accelerating their gene expression levels. We also confirmed that the IgM production by transcription-suppressed HB4C5 cells was facilitated by jellyfish collagen (Nishimoto et al, 2008). These findings suggest that jellyfish collagen would stimulate not only the transcription but also translational activity.…”
Section: Introductionsupporting
confidence: 79%
“…So far, we have found some components in foodstuffs such as lysozyme in hen egg, proteose-peptone component 3 fragment in fermented bovine milk, collagen in jellyfish, and ribulose-1,5-bisphosphate carboxylase/oxygenase in kale have Ig production-stimulating effect on human peripheral blood lymphocytes in vitro or on mice in vivo (Murakami, Sasaki, & Sugahara, 1997;Nishi et al, 2011;Sugahara et al, 2005Sugahara et al, , 2006. As for the lysozyme and collagen, we have also identified these modes of action of immunostimulatory effect (Nishimoto et al, 2008;Sugahara, Murakami, Yamada, & Sasaki, 2000).…”
Section: Introductionmentioning
confidence: 65%
“…We have found that jellyfish collagen, an Ig productionstimulating substance, promotes IgM production not only by up regulating transcription activity but also by enhancing translation activity. 7) Hence, yellowtail heart extract may also affect translation as well as transcription activity. It is also possible that stimulated cell proliferation due to yellowtail heart extract results in accelerated IgM production, as for jellyfish collagen, 6) but this is unlikely because the cultivation period of HB4C5 cells with yellowtail heart extract was no more than 6 h in this study.…”
Section: Resultsmentioning
confidence: 99%
“…We examined the mode of action of jellyfish collagen and found that it stimulated not only transcription activity, but also translation activity accelerating Ig production. 7) Other IPSFs from foodstuffs and natural products have been screened by many research groups. [8][9][10] In the course of fish processing, the viscera of fish are normally discarded.…”
mentioning
confidence: 99%